Counter-Learning Under Oppression - Ihan Kucukaydin (Adult Education Research Conference, 2008)
This qualitative study utilized narrative analysis to explore the counter-learning of an oppressed Kurdish woman from Turkey. Critical constructivism was used to analyze counter-learning and Frankfurt School-based Marcusian critical theory was used to analyze the socio-political context and its impact on the oppressed.
Keywords: Key issues for adult education theory and practice are highlighted. counter-learning; oppression; Kurdish woman; Marcuse